Numerical simulation study on multifield coupling of enhanced geothermal systems under different fracture characteristics - Hanbo Cui; Xintong Jiang; Zongyun Mo; Shenghao Guo; Changshuang Zhao; Weitan Zhuang; Fei Guo (PLoS ONE, 2025)
Fractures are key geological features in hot dry rock structures and fulfill a decisive role in determining productivity and reservoir stability. Adopting the Xudong fault zone in the Songliao Basin as the research object, a multifracture heat extraction model was constructed using COMSOL software to systematically analyze productivity and various field under different numbers and locations of horizontal and vertical fractures. Moreover, the influences of vertical fracture connectivity and the characteristics of seepage and heat transfer between the upper and lower rock layers on the temperature field were evaluated. The findings are as follows: (1) The production flow obtained with nine horizontal fractures is 2.25 to 2.28 times that obtained with four horizontal fractures. Increasing the number of horizontal fractures also increases the production temperature and heat extraction efficiency at the early stages of heat extraction but reduces productivity at the later stages and adversely affects reservoir stability. After 30 years of heat extraction, the production temperature, average subsidence, maximum subsidence, and average in situ stress obtained with nine horizontal fractures are 79.38% and 1.87, 1.61, and 1.45 times, respectively, those obtained with four horizontal fractures. (2) The influence of the number of vertical fractures on the geothermal reservoir characteristics is similar to but slightly smaller than that of horizontal fractures. However, the influences of vertical fractures on the production flow at the early stages and the maximum reservoir temperature at the later stages are opposite to those of horizontal fractures. When vertical fractures are located close to the injection well, productivity is low at the early stages but high at the later stages. The maximum subsidence, average in situ stress, and maximum in situ stress slightly increase, whereas the average subsidence decreases. (3) After 30 years of heat extraction, the average reservoir temperature is highest when seepage and heat transfer between the upper and lower rock layers occur and when vertical fractures do not penetrate the reservoir. When these conditions are reversed, the average temperature is lowest, with the former approximately 0.42°C higher than the latter. The findings of this study provide a reference for the construction of reservoir fracture systems.